Mitochondrial and nuclear DNA phylogeography of two cupped oysters Crassostrea gigas and Crassostrea angulata - Boudry, Pierre; Huvet, Arnaud (Conference Biology & Evolution of the Bivalvia, 1999)
The taxonomic status of Crassostrea angulata and Crassostrea gigas has long been a matter of controversy. Morphological and physiological similarities, as well as homogeneity in allelic frequencies on allozymes between the populations of the two taxa, lead most authors to suggest to regroup of the two within the same species. European and Asian populations of C. gigas and C. angulata have been studied using microsatellite and mitochondrial DNA markers. The analysis of genetic distances and the distribution of allelic and haplotype frequencies revealed a differentiation between the populations of C. gigas and C. angulata. The data allowed the construction of Neighbor-joining trees for each of the two types of markers. Similar topologies appeared with data on both genomes showing two clusters, but mitochondrial DNA presented much higher genetic differentiation among taxa than microsatellites. The first cluster included the French and Japanese populations and the second the Taiwanese and Portuguese populations. The Asiatic origin of Crassostrea angulata taxa is therefore confirmed. Despite their history, European populations of C. angulata did not show any significant reduction of variability compared to Asian populations.